Aplikasi Pencarian Biografi Tokoh Politik Indonesia Berbasis Mobile Dengan Algoritma Colussi - Novia Intan Pratiwi; Nelly Astuti Hasibuan; Saidi Ramadan Siregar (STMIK Budi Darma, 2020)
The Indonesian state is a democratic country in running its government. In carrying out its democratic system, the community plays an important role in this. One example is in the pilkada (regional head elections) or elections (general elections) in a period of 5 years. At the time of entering the 'political party' season, many photos of political candidates were seen pasted through leaflets or billboards on the streets and conducting campaign visits, this was done by prospective leaders with the aim of being known to the public and close to the people who would be choose it. The reality on the ground, many people who do not know the prospective leaders who nominate themselves to become politicians in Indonesia. The string matching algorithm applied in this study is the colussi algorithm. The colossi algorithm is a development of the knuth-morris-pratt algorithm.